2 Sam 14:16: STOP THE WICKED MAN - Oosthuizen, Rudolph (Scriptura, 1999)
The renewed call for relevance in the so-called new South Africa renders possible an exciting new stage in the development of Old Testament scholarship. Reading the Bible (2 Sam 14:1-24) from a perspective informed by our own context, Africa, sheds new light on the understanding of the text and allows the biblical and African views of reality to interact in the process of interpretation. Old Testament scholarship needs to develop models of reading the Bible creatively and effectively in the South African (African) context.